SARS-CoV-2 genomic surveillance in Malaysia: displacement of B.1.617.2 with AY lineages as the dominant Delta variants and the introduction of Omicron during the fourth epidemic wave - Nor Azila, Muhammad Azami; David, Perera; Ravindran, Thayan; Sazaly, AbuBakar; I-Ching, Sam; Mohd Zaki, Salleh; Mohd Noor, Mat Isa; Nurul Syakima, Ab Mutalib; Kiing Aik, Wong; Jeyanthi, Suppiah; Kim-Kee, Tan; Yoke Fun, Chan; et al. (Elsevier, 2022)
Objectives This study reported SARS-CoV-2 whole genome sequencing results from June 2021 to January 2022 from seven genome sequencing centers in Malaysia as part of the national surveillance program.